Group dynamics motivation to increase exercise intensity with a virtual partner - Stephen Samendinger; Christopher R. Hill; Norbert L. Kerr; Brian Winn; Alison Ede; James M. Pivarnik; Lori Ploutz-Snyder; Deborah L. Feltz (Elsevier, 2019)
Background: The effect of the Köhler group dynamics paradigm (i.e., working together with a more capable partner where one's performance is indispensable to the team outcome) has been shown to increase motivation to exercise longer at a strength task in partnered exercise video games (exergames) using a software-generated partner (SGP). However, the effect on exercise intensity with an SGP has not been investigated. The purpose of this study was to examine the motivation to maintain or increase exercise intensity among healthy, physically active middle-aged adults using an SGP in an aerobic exergame. Methods: Participants (n = 85, mean age = 44.9 years) exercised with an SGP in a 6-day cycle ergometer protocol, randomly assigned to either (a) no partner control, (b) superior SGP who was not a teammate, or (c) superior SGP as a teammate (team score was dependent on the inferior member). The protocol alternated between 30-min continuous and 4-min interval high-intensity session days, during which participants could change cycle power output (watts) from target intensity to alter distance and speed. Results: Mean change in watts from a targeted intensity (75% and 90% maximum heart rate) was the primary dependent variable reflecting motivational effort. Increases in performance over baseline were demonstrated without significant differences between conditions. Self-efficacy and enjoyment were significantly related to effort in the more intense interval sessions. Conclusion: Under these conditions, no Köhler effect was observed. Exercise performance during the higher-intensity interval format is more closely related to enjoyment and self-efficacy beliefs compared to the continuous sessions. Keywords: Exercise intensity, Köhler effect, Motivation, Software-generated partner